Glass-ceramics with γ-Ga2O3:Co2+ nanocrystals: saturable absorber for 1.5–1.7 μm Er lasers. (13th February 2015) - Loiko, P A; Dymshits, O S; Vitkin, V V; Skoptsov, N A; Kharitonov, A A; Zhilin, A A; Alekseeva, I P; Zapalova, S S; Malyarevich, A M; Glazunov, I V; Yumashev, K V
Abstract: Transparent glass-ceramics containing γ -Ga2 O3 :Co 2+ nanosized (7–12 nm) crystals are synthesized in a lithium gallium silicate system. Their spectroscopic and nonlinear properties are studied. The absorption band related to the 4 A2g ( 4 F) → 4 T1g ( 4 F) transition of Co 2+ ions in tetrahedral sites for these glass-ceramics is red-shifted up to 1.8 μ m. The absorption saturation fluence is determined to be 0.8 J cm −2 . The developed glass-ceramics are used for passive Q-switching of diode-pumped Er, Yb:glass laser delivering 1.75 mJ 25 ns-long pulses at 1540 nm.